Human disease-protein network - Cheng, Yangmei; Zhang, Hao (Current proteomics, 2018)
Background: Using system biology data to investigate diseases is a tendency. In consideration - that protein is the functional unit of human body in molecule...
Gesehen am 06.04.2020